Vorticity Recirculation and Asymmetric Generation at a Small Headland With Broadband Currents. Issue 3 (18th March 2021) - Kovatch, Michael; Feddersen, Falk; Grimes, Derek J.; MacMahan, Jamie H.
Abstract: Fixed acoustic Doppler current profiler (ADCP) velocity measurements are used to investigate headland vorticity generation and recirculation in ∼20 m depth around the small (∼1 km) central California headland Pt. Sal. To reduce vorticity estimation noise, velocities are reconstructed from the first two Empirical Orthogonal Function modes representing ≈73% of the variance. Using fixed ADCPs, depth‐averaged vorticity is estimated west and south of Pt. Sal. Only one west‐location vorticity component is estimated, leading to negative vorticity bias for northward flow. The south location vorticity is consistent with estimates from parallel vessel transects on one day. The observed depth‐averaged flow V was primarily along‐bathymetric contours and varied ±0.2 ms −1 across subtidal and tidal frequency bands. The depth‐averaged normalized vorticity ζ ¯ / f varied ±8 across all frequency bands. Vorticity distributions are skewed with opposite sign at west and south locations, and ζ ¯ / f < − 1 is more likely at the west location. At both locations, depth‐averaged vorticity and velocity are inversely related, with relationship asymmetric with sign of V, indicating headland and farther upstream vorticity generation. Binned‐mean ζ ¯ / f depends on both V and its time‐derivative, and indicates vorticity recirculation across the headland. The ∼2 h vorticity adjustment timescale and the associated short excursion distances indicate vorticity generation between south and west locations. Potential vorticity changes across the headland are different for positive and negative V indicating headland asymmetric vorticity generation. Pt. Sal occupies a nondimensional parameter space that is unique relative to other well studied headlands. Plain Language Summary: Coastal ocean flows past topographic features, such as headlands and islands, lead to a variety of processes which can enhance how much mixing and stirring occurs and have implications on the movement of marine biota and sediment. One measure of this mixing and stirring is 'vorticity, ' which is a gauge of how fast the water spins. Observations from September and October 2017 are used to investigate how vorticity is created and moved around the small (∼1 km) central California headland Pt. Sal. Raw data are filtered using statistical methods to remove noise. Vorticity is estimated west and south of Pt. Sal from groups of fixed instruments measuring flow speed and direction. Separate vorticity observations from a pair of research vessels corroborate the fixed observations on a single day. Currents at the headland were a mix of oscillatory tidal (twice a day) and longer time‐scale flows. The generation of vorticity is found to be stronger for northward flow relative to southward flow. The vorticity can also recirculate back with the oscillatory tidal flow. Pt. Sal is a unique study site, especially relative to other well studied headlands which are either larger in size or in deeper water. Key Points: At a 1 km scale headland (Pt. Sal CA), depth averaged vorticity varied {plus minus}8f and was asymmetrically related to along‐headland flow Vorticity also depends on flow acceleration, indicating short (2 h) adjustment timescale, recirculation, and headland generation Estimated potential vorticity across the headland indicates asymmetric vorticity generation stronger for northward flow